The conservation value of urban green space habitats for Australian native bee communities. (July 2015) - Threlfall, Caragh G.; Walker, Ken; Williams, Nicholas S.G.; Hahs, Amy K.; Mata, Luis; Stork, Nigel; Livesley, Stephen J.
Highlights: We examine bee communities in three dominant urban green spaces. Bee assemblages in residential neighbourhoods were dominated by Apis mellifera. Suitable bee habitat was infrequently managed, and dominated by native vegetation. Simple changes to green space management can assist native bee conservation. Abstract: Networks of urban green space can provide critical resources for wild bees, however it is unclear which attributes of green spaces provide these resources, or how their management can be improved to benefit a diversity of bee species. We examined bee communities in three dominant urban green space habitats: (1) golf courses (2) public parks and (3) front gardens and streetscapes in residential neighbourhoods in Melbourne, Australia and assessed which local and landscape attributes influenced bee communities. There was a greater abundance and richness of bee species in public parks compared to golf courses and residential neighbourhoods, where the latter habitat was dominated by European Honeybees ( Apis mellifera) . The occurrence of A. mellifera was positively associated with increases in flowering and native plants. Ground-nesting Homalictus species occurred more frequently in older golf courses and public parks surrounded by low impervious surface cover, and with a low diversity of flowering plants. Cavity nesting, floral specialists within the Colletidae family occurred more often in green space habitats with greater native vegetation, and occurred infrequently in residential neighbourhoods. The lack of appropriate nesting habitat and dominance of exotic flowering plants in residential neighbourhoods appeared to positively impact upon the generalist A. mellifera, but negatively affected cavity and ground nesting floral specialist bee species (e.g. Halictidae and Colletidae). Our results highlight the need to include urban areas in pollinator conservation initiatives, as providing resources critical to diverse bee communities can assist in maintaining these key pollinators in urban landscapes.